Relationship between serum reactive oxidative metabolite level and skin reaction in an irradiated rat model. (May 2014) - Nomiya, Takuma; Kaneko, Takashi; Goto, Jun; Harada, Mayumi; Akamatsu, Hiroko; Hagiwara, Yasuhito; Ota, Ibuki; Nemoto, Kenji
Abstract Purpose. Ionizing radiation generates free radicals and reactive oxygen species that induce DNA damage in vivo. This study aimed to determine the relationship between serum reactive oxygen metabolite (ROM) levels and skin reaction after irradiation in a rat model. Methods and materials. I. Female Wistar rats were classified into 0 Gy (control), 2 Gy, and 30 Gy groups; serum ROM levels were measured in the very acute phase. II. Other female Wistar rats were classified into 0 Gy (control), 30 Gy, 50 Gy, and 70 Gy groups; serum ROM levels were measured before and 3, 7, 16, 24, 31, and 38 days after irradiation. Skin reaction was evaluated according to the SRS (0–5) twice every week. Results. Serum ROM levels in the subacute phase were significantly higher in the 50 and 70 Gy groups than in the 0 and 30 Gy groups [p = 0.029, repeated-measure analysis of variance (ANOVA)]. As expected, SRSs increased in the order of the 0 Gy, 30 Gy, 50 Gy, and 70 Gy groups and differed significantly among these groups (p < 0.001, repeated-measure ANOVA). Peak serum ROM levels were observed 16 days after irradiation in all irradiated groups and corresponded with the appearance of visible skin reaction after irradiation. Conclusions. Serum ROM levels may be useful for evaluating radiation damage in mammals. Further investigations are required to investigate changes in intracellular metabolism after irradiation at gene and protein levels.